PENGARUH UKURAN PERUSAHAAN, DEWAN KOMISARIS DAN CAPITAL INTENSITY TERHADAP EFFECTIVE TAX RATE (ETR) - Novianti, Dewi Ratna; Praptiningsih, Praptiningsih; Lastiningsih, Noegrahini (EQUITY, 2018)
This research is using quantitative study aimed to see whether there are influence of Firm Size, Board of Commissioners and Capital Intensity on Effective Tax Rate (ETR). The sample in this study a number of 67 manufacturing companies listed on the Indonesia Stock Exchange period 2014 – 2016 by using purposive sampling method. Data obtained from the financial reports in the publication. The number of sample obtained as many as 67 companies with a total sample of 201 samples. After reduce the data outlier, data eventually resulted in 147 samples ready to be analyzed and tested. Analysis technique used was multiple linier regression with a level of significance of 5%. The results of this study suggests that (1) Firm Size has significant effect on the Effective Tax Rate (ETR), (2) Board of Commissioners was not significant effect on Effective Tax Rate (ETR), (3)Capital Intensity effect significantly to Effective Tax Rate (ETR).